Softened and flexible biodegradable poly(lactic acid) and its electromechanical properties for actuator application - Natlita Thummarungsan (2018)
Copyright © 2016 Elsevier Ltd. All rights reserved. Poly (lactic acid) (PLA) is a biodegradable polymer with high stiffness presenting a limitation for using in actuator applications. Adding a plasticizer is one way to solve this problem to enhance flexibility and improve electromechanical properties of pristine PLA. In this work, the PLA films were prepared via a simple solvent casting method. The influences of plasticizer type and electric field strength on electromechanical behavior of PLA films were investigated by the melt rheometer and bending measurement. For the PLA films filled with dibutyl phthalate (DBP), the storage modulus, G', immediately increased towards its steady state and rapidly recovered to its original value with and without electric field, respectively, which can be referred to a reversible system. On the other hand, the PLA film with Tween 20 processed the highest ∆G׳/G׳0 of 1.34 due to the available amount of polarized groups. In the bending measurement, the dielectrophoresis forces of plasticized PLA films were found to increase with increasing electric field where the deflections occurred towards anode side as the polarized groups generated negative charges. The DBP_PLA1.5D film exhibited the greatest bending and dielectrophoresis force. Thus, the biodegradable PLA along with DBP combine to have a great potential towards actuator application.